The Correlation Between Parents’ Language Attitudes and Students’ EnglishAchievement - Hasymi Romanov, Ali (U-Jet Unila Journal of English Language Teaching, 2024)
This study aimed to explore the relationship between parents’ language attitudes and students’ English achievement. It was conducted at Swadhipa 1 Natar Junior High School, with 27 parents and ninth-grade students as subjects. Data on language attitudes were collected through questionnaires, while English achievement data were obtained from the first semester English report cards of the academic year 2023-2024. The research applied an ex-facto design correlation study, and the results were analyzed using Pearson correlation.The findings revealed a negative correlation between parents’ language attitudes and students’ English achievement. The analysis indicated a correlation coefficient of -0.62 (normalized parents' attitude score) and -0.61 (original), which, within the Pearson correlation range, approaches -1. This suggests a strong negative relationship, as the coefficient value exceeds - 0.5. Consequently, in this study, parents’ language attitudes cannot indicate their child's English achievement level.